Development of Teaching Materials Based on People's Stories Assisted In the Graphics of 5th Grade Students Primary School Muhammadiyah 01 Kota Binjai - Indah Gustia Lubis; Abdurahman Adisaputera; Rosmala Dewi (BIRCU, 2020)
This research aims to: (1) Analyze how effective the use of teaching materials is based on folktales assisted with serial images. (2) Analyze how the feasibility of teaching materials based on folklore based on serial images developed to improve learning outcomes. This research uses Borg & Gel development research. Based on the results of the validity of material experts 85.42%, 85.7% design experts, and 94.44% linguists. From the results of the validation of teaching materials developed, the teaching materials based on folklore with serial images are included in the very good criteria and are declared to be effective and appropriate for use. Based on the completeness data of student learning outcomes before using the average value obtained reached 62, while after using individual completeness and classical average reached 85 with a gain score of 0.70 into the high category. And the questionnaire responses of students about the effectiveness of teaching materials reached 88% of 25 students. Based on this data teaching material based on rocky folktales is said to be effectively used in learning with the assumption that Indonesian students score higher when using material.